Demographic, Health and Pandemic-Related Determinants of COVID-19 Vaccination Intention Among Filipino Emerging Adults. Issue 3 (June 2022) - Cleofas, Jerome V.; Oducado, Ryan Michael F.
Emerging adults have become more susceptible to COVID-19 because of the emergence of the Delta and Omicron variants. Vaccination can help protect them from contracting the virus. However, in the Philippines, vaccine acceptance rates are low. This cross-sectional study sought to determine the demographic, health, and pandemic-related determinants of COVID-19 vaccination intention among Filipino emerging adults. A total of 1692 Filipinos aged 18–24 years old participated in this study by answering an online survey. Findings reveal that 57.03% of the respondents do not intend to complete their COVID-19 vaccinations. Logistic regression analysis results suggest that less than "very good" self-reported health, lower life satisfaction, previous exposure to a COVID-19 patient, and lower pandemic fatigue were associated with greater odds of intending to vaccinate among Filipino emerging adults ( p < 0.05).